Mixture material and application thereof in preparation of kettle-bell
By using a mixture of specific raw materials to make the inner core of the kettlebell and reinforcing the rubber coating, it solves the problem of easy damage to existing kettlebell materials and achieves higher mechanical properties and drop resistance.
Patent Information
- Application Number
- CN202411442541.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
AI Technical Summary
The existing kettlebells are mostly cast iron, which sounds loud and has a high impact when falling, which can easily damage the ground; while the rubber kettlebells lack mechanical properties and are prone to deformation or breakage.
A mixture of materials made from specific raw materials, including high-strength Portland cement, ore, ore sand, mixed fibers, epoxy resin adhesive, wood particles, composite plastic masterbatch, steel wire pellets, iron powder, perlite and water. The inner core of the kettlebell is formed through vibration and curing processes, and is subsequently reinforced with a rubber coating.
The mechanical properties and drop resistance of the kettlebell are improved, the impact force when dropped is reduced, the service life is extended, and the production cost is reduced.
Smart Images

Figure BDA0005086736060000151
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of fitness equipment, and in particular to a mixture material and its application in the preparation of kettlebells. Background Art
[0002] Kettlebell is a kind of sports equipment used to enhance muscle strength training. Kettlebells are mostly made of cast iron. Due to the heavy weight of cast iron, the sound of the kettlebell falling is loud during kettlebell training, which causes a great impact force on the kettlebell itself and is also easy to cause damage to the ground.
[0003] In order to prevent the kettlebell from damaging the floor when it falls, a full-rubber kettlebell becomes a better choice. However, due to the light specific gravity and insufficient mechanical properties of rubber, it is prone to deformation and breakage during product use.
[0004] Putting a rubber sleeve on the metal can reduce the impact when the kettlebell falls, but the integrity is not strong and the rubber sleeve is easy to move and fall off. Filling the rubber outer layer with inorganic fillers can improve the integrity of the kettlebell. Concrete has the prospect of being used as a filler in kettlebells because of its large specific gravity and good mechanical strength. However, the tensile strength of general concrete is low and the material is brittle. When subjected to tensile forces such as being thrown, it is easy to crack or even break under external impact, affecting the stability of the structure. Summary of the invention
[0005] The present application aims to overcome at least one of the defects of the prior art and provide a mixture material and its application in the preparation of kettlebells. By matching specific raw materials, the prepared mixture material has a larger specific gravity while improving the shatter resistance of concrete, and can be used to make kettlebells.
[0006] In a first aspect, the present invention provides a mixture material, which is realized by the following technical solutions:
[0007] A mixture material comprises the following raw materials in parts by weight:
[0008] 20-40 parts of high-strength Portland cement, 10-20 parts of ore, 10-20 parts of mineral sand, 5-10 parts of mixed fiber, 2-3 parts of epoxy resin adhesive, 5-15 parts of wood particles, 5-15 parts of composite plastic masterbatch, 5-10 parts of cut wire shot, 3-8 parts of iron powder, 5-15 parts of perlite, 20-40 parts of water;
[0009] Wherein, the hybrid fiber comprises graphene fiber and basalt fiber in a mass ratio of (2-3):(1-2);
[0010] The composite plastic masterbatch comprises the following raw materials in parts by weight: 40-45 parts of polycarbonate carrier resin, 1-2 parts of dispersant, 4-6 parts of aramid fiber, 1-2 parts of modified nano zinc oxide, and 2-3 parts of copolymerized methyl methacrylate;
[0011] The dispersant is a silicone-modified polyurethane acrylate oligomer;
[0012] The preparation method of the organosilicon-modified polyurethane acrylate oligomer comprises the following steps:
[0013] 40-50 parts of polyurethane acrylate oligomer, 8-10 parts of pentaerythritol triacrylate, and 2-3 parts of 3-aminopropyltriethoxysilane are mixed according to weight parts, and heated in an oil bath at a speed of 200 rpm / min until the temperature reaches 150-160° C., and 0.3-0.6 parts of dicumyl peroxide solution are added dropwise at a speed of 30 drops / min. After reacting for 4-6 hours, a silicone-modified polyurethane acrylate oligomer is obtained;
[0014] The preparation method of the modified nano zinc oxide comprises the following steps:
[0015] B1. Ultrasonic dispersion of nano zinc oxide in a mixed solution of anhydrous ethanol and deionized water (8-9):1 mass ratio, and adding coupling agent KH-550 under stirring, raising the temperature to 70-80 ° C, constant temperature magnetic stirring for 5-8h, centrifugation, washing, and drying to obtain organosilicon-modified nano zinc oxide;
[0016] B2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4h, and dried and ground after the reaction is completed;
[0017] B3. Add the graphene pretreated in step B2 to ethanol for ultrasonic dispersion, add the organosilicon-modified nano zinc oxide prepared in step B1, stir rapidly at 25-35°C to allow it to react fully, centrifuge, wash several times with anhydrous ethanol, dry in vacuum, and grind to obtain modified nano zinc oxide.
[0018] A mixture material according to an embodiment of the present application has at least the following beneficial effects:
[0019] The mixed material of the present application is matched with different raw materials. The graphene fiber in the mixed fiber has good mechanical strength, which can be 200 times that of ordinary steel. The graphene fiber has strong resistance to chemical corrosion and oxidation, and can withstand corrosion from various strong acids and strong alkalis. The basalt fiber in the mixed fiber has good corrosion resistance, high temperature resistance and thermal shock stability, high elastic modulus and tensile strength. High-strength silicate cement is blended with the mixed fiber so that the mixed fiber can be effectively filled into the gaps of particles such as ore, mineral sand, wood particles, perlite, etc. in the cement slurry. At the same time, epoxy resin adhesive is added for bonding. The epoxy resin adhesive can penetrate into the tiny pores of the concrete matrix and form mechanical bite and chemical bonding with the concrete, thereby enhancing the bonding force between the fiber and the concrete, promoting the combination of the fiber and the cement, and enhancing the strength and stability of the mixed material. When the mixed material is subjected to external force, the fiber can bear part of the tensile stress, thereby reducing the stress of the cement matrix. This mechanical action forms a dynamic equilibrium state between the fiber and the cement matrix, which is conducive to the stable combination of the two.
[0020] The high-strength silicate cement of the present application has high impermeability and erosion resistance, can effectively resist the penetration and erosion of moisture and harmful substances, helps to reduce the formation of pores and defects inside the mixture material, and protects the stability and durability of the mixture material structure. In addition, the high-strength silicate cement has high wear resistance, can withstand greater mechanical wear and impact, and can improve the drop resistance of the mixture material.
[0021] The ore, mineral sand, wire cut shot, iron powder and perlite of the present application can improve the mechanical strength of the mixture material and increase the specific gravity of the mixture material. The wood particles and elastic resin particles of the present application can improve the elasticity and impact resistance of the mixture material. By matching and mixing the above raw materials, the mixture material is suitable for use as a filler for fitness equipment.
[0022] The composite plastic masterbatch of the present application is composited with raw materials such as polycarbonate carrier resin, aramid fiber, copolymerized methyl methacrylate, etc. The polycarbonate carrier resin has strong impact resistance and good mechanical properties, and can enhance the impact resistance of the mixture material. The aramid fiber has good mechanical properties, excellent flame retardancy, heat resistance and stable chemical properties. The copolymerized methyl methacrylate has strong toughness. The combination of the raw materials can further enhance the strength of the composite plastic masterbatch, thereby improving the drop and impact resistance of the mixture material.
[0023] The polycarbonate carrier resin has poor fluidity. The silicone-modified polyurethane acrylate oligomer in this application can well improve the compatibility of the components of the system, promote plasticization, improve processing fluidity, reduce the torque of processing equipment, reduce processing energy consumption, improve production efficiency, and significantly improve the surface properties of the composite plastic masterbatch.
[0024] Modified nano zinc oxide is used as a filler in the composite plastic masterbatch in the present application. The nano material can enhance the mechanical properties of polycarbonate due to its large specific surface area and high adsorption performance; zinc oxide can effectively improve the antioxidant and corrosion resistance; silicone can increase the dispersion of nano zinc oxide in the polycarbonate matrix, and improve the elasticity, wear resistance, corrosion resistance and flame retardancy of the composite plastic masterbatch; after the graphene is acidified, the surface will be oxidized into carboxyl groups, which will combine with the nano zinc oxide modified by silicone, reducing the problem of easy agglomeration of graphene. The layered structure of graphene makes the mixing between the filler and the resin more complete, thereby improving the high temperature resistance and tensile strength of the composite plastic masterbatch.
[0025] According to some embodiments of the present application, the method for preparing the composite plastic masterbatch comprises the following steps:
[0026] S1. According to the ratio of polycarbonate carrier resin, dispersant, aramid fiber, modified nano zinc oxide, copolymerized methyl methacrylate was added to a high-speed mixer and stirred evenly to obtain a granulation raw material;
[0027] S2. The granulated raw materials in step S1 are subjected to twin-screw granulation to obtain composite plastic masterbatch.
[0028] Furthermore, the rotation speed of the high-speed mixer in step S1 is 2500-2800 rpm / min.
[0029] Furthermore, the temperature of the high-speed mixer in step S1 is 50-100°C.
[0030] Furthermore, the rotation speed of the twin-screw granulation in step S2 is 600-700 rpm / min.
[0031] Furthermore, the temperature of the twin-screw granulation in step S2 is 200-240°C.
[0032] According to some embodiments of the present application, the mass ratio of the nano zinc oxide, the anhydrous ethanol and the coupling agent KH-550 in step B1 is 1:(8-10):(0.1-0.2).
[0033] According to some embodiments of the present application, the strength grade of the high-strength silicate cement is P.O52.5.
[0034] According to some embodiments of the present application, the diameter of the hybrid fiber is 10 μm-1000 μm.
[0035] According to some embodiments of the present application, the length of the mixed fiber is 0.5 cm-2 cm.
[0036] Blending of small diameter and short length fibers can more effectively fill the gaps between particles in the cement paste, further improving the strength and stability of the mixture material.
[0037] According to some embodiments of the present application, the wood particles are selected from at least one of ash, beech, camphor, walnut, oak, birch, fir, elm, and redwood.
[0038] According to some embodiments of the present application, the average particle size of the wood particles is 3-6 mm. Wood particles within this particle size range are easy to combine with cement slurry, taking into account the elasticity of the wood particles and the strength of the mixed material, thereby enhancing the impact resistance of the mixed material.
[0039] According to some embodiments of the present application, the average particle size of the ore is 5-15 mm.
[0040] According to some embodiments of the present application, the average particle size of the perlite is 5-15 mm.
[0041] If the particle size of aggregates such as ore and perlite is too large, the gaps between the large particles will be difficult to be filled with cement slurry, affecting the strength of the mixed material. Conversely, if the particle size of aggregates such as ore and perlite is too small, the mixed raw materials are mainly cement slurry, and the friction between the particles is too small, resulting in reduced bonding performance between the mixed raw materials, which will also affect the strength of the mixed material.
[0042] According to some embodiments of the present application, the method for preparing the mixture material is:
[0043] A1. According to parts by weight, high-strength Portland cement, ore, ore sand, mixed fiber, epoxy resin adhesive, wood particles, composite plastic masterbatch, cut wire shot, iron powder, perlite and water were mixed and stirred for 10 minutes to obtain a mixed raw material;
[0044] A2. The mixed raw materials were vibrated at a frequency of 200-300 Hz for 2-4 minutes using a vibrating rod, and after 21 days of curing and watering 3 times a day, a mixture material was obtained.
[0045] In a second aspect, an embodiment of the present application provides a kettlebell comprising the mixture material.
[0046] A kettlebell comprising the mixture material according to an embodiment of the present application has at least the following beneficial effects:
[0047] The kettlebell of the present application has good mechanical properties and is not easy to deform. It also has good drop resistance and is not easy to break when impacted by external forces, and has a long service life.
[0048] According to some embodiments of the present application, the kettlebell includes a skeleton and a rubber coating layer.
[0049] Furthermore, the material of the skeleton is steel bars. The expansion coefficients of the steel bars and the mixture material are similar, so they can be better integrated, and gaps are less likely to appear during subsequent use, thereby improving the bonding strength.
[0050] Furthermore, the frame includes a spherical frame and a U-shaped handle.
[0051] Furthermore, the material of the rubber coating is selected from one of synthetic rubber, rubber particles and rubber plastic. Rubber, rubber particles and rubber plastic can further enhance the elasticity of the kettlebell, and the kettlebell is not easy to damage the floor when it falls.
[0052] In a third aspect, the present application provides a method for preparing the kettlebell, which is implemented by the following technical solutions:
[0053] A method for preparing a kettlebell comprises the following steps:
[0054] (1) connecting the spherical frame and the U-shaped handle to form a frame;
[0055] (2) mixing high-strength silicate cement, ore, mineral sand, mixed fiber, epoxy resin adhesive, wood particles, composite plastic masterbatch, cut wire shot, iron powder, perlite and water according to weight parts, and stirring for 10 minutes to obtain a mixed raw material;
[0056] (3) filling the skeleton and the mixed raw materials into a kettlebell mold, vibrating the mold at a frequency of 200-300 Hz for 2-4 minutes using a vibrating rod, curing the mold for 21 days and watering the mold 3 times a day to obtain a kettlebell core;
[0057] (4) Using a rubber coating mold, the outer layer of the kettlebell inner core is coated with rubber by heating and vulcanization, wherein the upper mold temperature is 145° C. and the lower mold temperature is 145° C. to obtain a kettlebell.
[0058] The method for preparing a kettlebell according to the embodiment of the present application has at least the following beneficial effects:
[0059] The present application adopts the method of solidifying the filler first and then coating with rubber to prepare the kettlebell, which can ensure the mechanical strength of the inner core of the kettlebell while taking into account the drop resistance. The kettlebell has good integrity. When in use, the inner core of the kettlebell and the rubber coating layer are not easy to fall off, and the kettlebell is not easy to deform or break. The preparation method of the present application has simple steps, does not require the use of complex production equipment, has low cost, and is suitable for industrial production.
[0060] The present application further improves the mechanical strength of the kettlebell by solidifying the skeleton inside the mixture material, making it less likely to break or deform when impacted by external forces.
[0061] In the present application, the mixed raw materials are evenly distributed in the mold through the vibration of the vibrating rod, and at the same time, bubbles in the mixed raw materials are easily discharged, so that the mixed raw materials are fully dense, and the molded mixed material is more solid and not easy to break. DETAILED DESCRIPTION
[0062] To make the purpose, technical solution and advantages of the present application clearer, the following will be further described in detail in conjunction with specific embodiments. The embodiments described here are only part of the embodiments of the present application and cannot be understood as limiting the scope of protection of the present application.
[0063] Preparation Example 1 of Silicone-Modified Polyurethane Acrylate Oligomer
[0064] Preparation of silicone-modified polyurethane acrylate oligomer:
[0065] 45 parts of polyurethane acrylate oligomer, 9 parts of pentaerythritol triacrylate and 3 parts of 3-aminopropyltriethoxysilane were mixed according to weight parts, and heated in an oil bath with stirring at a speed of 200 rpm / min until the temperature reached 155°C. 0.5 parts of diisopropyl peroxide solution was added dropwise at a rate of 30 drops / min. After reacting for 5 hours, a silicone-modified polyurethane acrylate oligomer was obtained.
[0066] Preparation Example 2 of Silicone-Modified Polyurethane Acrylate Oligomer
[0067] Preparation of silicone-modified polyurethane acrylate oligomer:
[0068] 50 parts of polyurethane acrylate oligomer, 8 parts of pentaerythritol triacrylate and 3 parts of 3-aminopropyltriethoxysilane were mixed according to weight parts, and heated in an oil bath with stirring at a speed of 200 rpm / min until the temperature reached 150°C. 0.6 parts of diisopropyl peroxide solution was added dropwise at a rate of 30 drops / min. After reacting for 4 hours, a silicone-modified polyurethane acrylate oligomer was obtained.
[0069] Preparation Example 1 of Modified Nano Zinc Oxide
[0070] Preparation of modified nano zinc oxide:
[0071] B1. 10 g of nano zinc oxide was ultrasonically dispersed in 100 g of a mixed solution of anhydrous ethanol and deionized water in a mass ratio of 9:1, and 2 g of coupling agent KH-550 was added under stirring, the temperature was raised to 75°C, and constant temperature magnetic stirring was performed for 6 hours. After centrifugation, washing, and drying, organosilicon-modified nano zinc oxide was obtained;
[0072] B2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4h, and dried and ground after the reaction is completed;
[0073] B3. Add the graphene pretreated in step B2 to ethanol for ultrasonic dispersion, add the organosilicon-modified nano zinc oxide prepared in step B1, stir rapidly at 30°C to allow it to react fully, centrifuge, wash several times with anhydrous ethanol, dry in vacuum, and grind to obtain modified nano zinc oxide.
[0074] Preparation Example 2 of Modified Nano Zinc Oxide
[0075] Preparation of modified nano zinc oxide:
[0076] B1. 10 g of nano zinc oxide was ultrasonically dispersed in 90 g of a mixed solution of anhydrous ethanol and deionized water in a mass ratio of 8:1, and 1 g of coupling agent KH-550 was added under stirring, the temperature was raised to 80°C, and constant temperature magnetic stirring was performed for 8 hours. After centrifugation, washing, and drying, organosilicon-modified nano zinc oxide was obtained;
[0077] B2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4h, and dried and ground after the reaction is completed;
[0078] B3. Add the graphene pretreated in step B2 to ethanol for ultrasonic dispersion, add the organosilicon-modified nano zinc oxide prepared in step B1, stir rapidly at 25°C to allow it to react fully, centrifuge, wash several times with anhydrous ethanol, dry in vacuum, and grind to obtain modified nano zinc oxide.
[0079] Modified Nano Zinc Oxide Comparative Example 1
[0080] Preparation of modified nano zinc oxide:
[0081] 10 g of nano zinc oxide was ultrasonically dispersed in 100 g of a mixed solution of anhydrous ethanol and deionized water in a mass ratio of 9:1, and 2 g of coupling agent KH-550 was added under stirring. The temperature was raised to 75°C and magnetic stirring was performed at a constant temperature for 6 hours. After centrifugation, washing and drying, organosilicon-modified nano zinc oxide was obtained.
[0082] Preparation Example 1 of Composite Plastic Masterbatch
[0083] Preparation of composite plastic masterbatch: Select the following raw materials by weight: 43 parts of polycarbonate carrier resin, 2 parts of organosilicon-modified polyurethane acrylate oligomer prepared in Preparation Example 1 of organosilicon-modified polyurethane acrylate oligomer, 5 parts of aramid fiber, 2 parts of modified nano zinc oxide prepared in Preparation Example 1 of modified nano zinc oxide, and 3 parts of copolymerized methyl methacrylate;
[0084] S1. According to the ratio, a polycarbonate carrier resin, a silicone-modified polyurethane acrylate oligomer, an aramid fiber, a modified nano zinc oxide, and a copolymer of methyl methacrylate were added to a high-speed mixer and stirred at a speed of 2700 rpm / min and a temperature of 80 ° C to obtain a granulation raw material;
[0085] S2. The granulated raw materials in step S1 are subjected to twin-screw granulation at a rotation speed of 650 rpm / min and a temperature of 230° C. to obtain composite plastic masterbatch.
[0086] Preparation Example 2 of Composite Plastic Masterbatch
[0087] Preparation of composite plastic masterbatch: Select the following raw materials by weight: 40 parts of polycarbonate carrier resin, 2 parts of organosilicon-modified polyurethane acrylate oligomer prepared in Preparation Example 1 of organosilicon-modified polyurethane acrylate oligomer, 4 parts of aramid fiber, 2 parts of modified nano zinc oxide prepared in Preparation Example 1 of modified nano zinc oxide, and 2 parts of copolymerized methyl methacrylate;
[0088] S1. According to the ratio, a polycarbonate carrier resin, a silicone-modified polyurethane acrylate oligomer, an aramid fiber, a modified nano zinc oxide, and a copolymer of methyl methacrylate were added to a high-speed mixer and stirred at a speed of 2800 rpm / min and a temperature of 50 ° C to obtain a granulation raw material;
[0089] S2. The granulated raw materials in step S1 are subjected to twin-screw granulation at a rotation speed of 700 rpm / min and a temperature of 200° C. to obtain composite plastic masterbatch.
[0090] Composite plastic masterbatch comparative example 1
[0091] Preparation of composite plastic masterbatch: Select raw materials by weight: 43 parts of polycarbonate carrier resin, 2 parts of organosilicon-modified polyurethane acrylate oligomer prepared in Preparation Example 1 of organosilicon-modified polyurethane acrylate oligomer, 5 parts of aramid fiber, 2 parts of modified nano zinc oxide prepared in Comparative Example 1 of modified nano zinc oxide, and 3 parts of copolymerized methyl methacrylate;
[0092] S1. According to the ratio, a polycarbonate carrier resin, a silicone-modified polyurethane acrylate oligomer, an aramid fiber, a modified nano zinc oxide, and a copolymer of methyl methacrylate were added to a high-speed mixer and stirred at a speed of 2700 rpm / min and a temperature of 80 ° C to obtain a granulation raw material;
[0093] S2. The granulated raw materials in step S1 are subjected to twin-screw granulation at a rotation speed of 650 rpm / min and a temperature of 230° C. to obtain composite plastic masterbatch.
[0094] Composite plastic masterbatch comparative example 2
[0095] Preparation of composite plastic masterbatch: Select the following raw materials by weight: 43 parts of polycarbonate carrier resin, 5 parts of aramid fiber, 2 parts of modified nano zinc oxide prepared in Preparation Example 1 of modified nano zinc oxide, and 3 parts of copolymerized methyl methacrylate;
[0096] S1. According to the ratio of polycarbonate carrier resin, aramid fiber, modified nano zinc oxide, methyl methacrylate copolymer was added to a high-speed mixer, stirred at a speed of 2700 rpm / min, a temperature of 80 ° C, to obtain a granulation raw material;
[0097] S2. The granulated raw materials in step S1 are subjected to twin-screw granulation at a rotation speed of 650 rpm / min and a temperature of 230° C. to obtain composite plastic masterbatch.
[0098] Example 1
[0099] Preparation of mixture materials: Select the raw materials by weight: 30 parts of high-strength silicate cement, 15 parts of ore, 18 parts of mineral sand, 8 parts of mixed fiber, 2 parts of epoxy resin adhesive, 10 parts of wood particles, 10 parts of composite plastic masterbatch prepared in Example 1 of composite plastic masterbatch preparation, 7 parts of cut wire shot, 6 parts of iron powder, 9 parts of perlite, and 28 parts of water; wherein the mixed fiber is a mixture of graphene fiber and basalt fiber in a mass ratio of 3:2; the diameter of the mixed fiber is 10μm-1000μm; the length of the mixed fiber is 0.5cm-2cm; the wood particles are a mixture of camphor wood and oak in a weight ratio of 1:1; the average particle size of the wood particles is 5mm; the strength grade of the high-strength silicate cement is P.O52.5; the average particle size of the ore is 10mm; the average particle size of the perlite is 10mm;
[0100] A1. According to parts by weight, high-strength Portland cement, ore, ore sand, mixed fiber, epoxy resin adhesive, wood particles, composite plastic masterbatch, cut wire shot, iron powder, perlite and water were mixed and stirred for 10 minutes to obtain a mixed raw material;
[0101] A2. The mixed raw materials were vibrated at a frequency of 250 Hz for 3 minutes using a vibrating rod, and after 21 days of curing and watering 3 times a day, a mixed material was obtained.
[0102] Example 2
[0103] Preparation of mixture materials: Select the following raw materials by weight: 20 parts of high-strength silicate cement, 10 parts of ore, 20 parts of mineral sand, 10 parts of mixed fiber, 2 parts of epoxy resin adhesive, 15 parts of wood particles, 5 parts of composite plastic masterbatch prepared in Example 1 of composite plastic masterbatch preparation, 5 parts of cut wire shot, 8 parts of iron powder, 5 parts of perlite, and 20 parts of water; wherein the mixed fiber is a mixture of graphene fiber and basalt fiber in a mass ratio of 3:1; the diameter of the mixed fiber is 10μm-1000μm; the length of the mixed fiber is 0.5cm-2cm; the wood particles are selected from elm; the average particle size of the wood particles is 6mm; the strength grade of the high-strength silicate cement is P.O52.5; the average particle size of the ore is 5mm; the average particle size of the perlite is 15mm;
[0104] A1. According to parts by weight, high-strength Portland cement, ore, ore sand, mixed fiber, epoxy resin adhesive, wood particles, composite plastic masterbatch, cut wire shot, iron powder, perlite and water were mixed and stirred for 10 minutes to obtain a mixed raw material;
[0105] A2. The mixed raw materials were vibrated at a frequency of 200 Hz for 4 minutes using a vibrating rod, and after 21 days of curing and watering 3 times a day, a mixed material was obtained.
[0106] Example 3
[0107] Preparation of mixture materials: Select raw materials by weight: 40 parts of high-strength silicate cement, 20 parts of ore, 10 parts of mineral sand, 5 parts of mixed fiber, 3 parts of epoxy resin adhesive, 5 parts of wood particles, 15 parts of composite plastic masterbatch prepared in Example 1 of composite plastic masterbatch preparation, 10 parts of cut wire shot, 3 parts of iron powder, 15 parts of perlite, and 40 parts of water; wherein the mixed fiber is a mixture of graphene fiber and basalt fiber in a mass ratio of 2:2; the diameter of the mixed fiber is 10μm-1000μm; the length of the mixed fiber is 0.5cm-2cm; the wood particles are selected from walnut wood; the average particle size of the wood particles is 3mm; the strength grade of the high-strength silicate cement is P.O52.5; the average particle size of the ore is 15mm; the average particle size of the perlite is 5mm;
[0108] A1. According to parts by weight, high-strength Portland cement, ore, ore sand, mixed fiber, epoxy resin adhesive, wood particles, composite plastic masterbatch, cut wire shot, iron powder, perlite and water were mixed and stirred for 10 minutes to obtain a mixed raw material;
[0109] A2. The mixed raw materials were vibrated at a frequency of 300 Hz for 2 minutes using a vibrating rod, and after 21 days of curing and watering 3 times a day, a mixture material was obtained.
[0110] Comparative Example 1
[0111] Preparation of mixed materials: Select the following raw materials by weight: 30 parts of high-strength silicate cement, 15 parts of ore, 18 parts of mineral sand, 8 parts of mixed fiber, 2 parts of epoxy resin adhesive, 10 parts of wood particles, 7 parts of cut wire shot, 6 parts of iron powder, 9 parts of perlite, and 28 parts of water; wherein the mixed fiber is a mixture of graphene fiber and basalt fiber in a mass ratio of 3:2; the diameter of the mixed fiber is 10μm-1000μm; the length of the mixed fiber is 0.5cm-2cm; the wood particles are a mixture of camphor wood and oak in a weight ratio of 1:1; the average particle size of the wood particles is 5mm; the strength grade of the high-strength silicate cement is P.O52.5; the average particle size of the ore is 10mm; the average particle size of the perlite is 10mm;
[0112] A1. According to parts by weight, high-strength Portland cement, ore, ore, mixed fiber, epoxy resin adhesive, wood particles, cut wire shot, iron powder, perlite and water were mixed and stirred for 10 minutes to obtain a mixed raw material;
[0113] A2. The mixed raw materials were vibrated at a frequency of 250 Hz for 3 minutes using a vibrating rod, and after 21 days of curing and watering 3 times a day, a mixed material was obtained.
[0114] Comparative Example 2
[0115] Preparation of mixture materials: Select raw materials by weight: 30 parts of high-strength silicate cement, 15 parts of ore, 18 parts of mineral sand, 8 parts of mixed fiber, 2 parts of epoxy resin adhesive, 10 parts of wood particles, 10 parts of composite plastic masterbatch prepared in Example 1 of composite plastic masterbatch, 7 parts of cut wire shot, 6 parts of iron powder, 9 parts of perlite, and 28 parts of water; wherein the mixed fiber is a mixture of graphene fiber and basalt fiber in a mass ratio of 3:2; the diameter of the mixed fiber is 10μm-1000μm; the length of the mixed fiber is 0.5cm-2cm; the wood particles are a mixture of camphor wood and oak in a weight ratio of 1:1; the average particle size of the wood particles is 5mm; the strength grade of the high-strength silicate cement is P.O52.5; the average particle size of the ore is 10mm; the average particle size of the perlite is 10mm;
[0116] A1. According to parts by weight, high-strength Portland cement, ore, ore sand, mixed fiber, epoxy resin adhesive, wood particles, composite plastic masterbatch, cut wire shot, iron powder, perlite and water were mixed and stirred for 10 minutes to obtain a mixed raw material;
[0117] A2. The mixed raw materials were vibrated at a frequency of 250 Hz for 3 minutes using a vibrating rod, and after 21 days of curing and watering 3 times a day, a mixed material was obtained.
[0118] Comparative Example 3
[0119] Preparation of mixture materials: Select raw materials by weight: 30 parts of high-strength silicate cement, 15 parts of ore, 18 parts of mineral sand, 8 parts of mixed fiber, 2 parts of epoxy resin adhesive, 10 parts of wood particles, 10 parts of composite plastic masterbatch prepared in Example 2 of composite plastic masterbatch, 7 parts of cut wire shot, 6 parts of iron powder, 9 parts of perlite, and 28 parts of water; wherein the mixed fiber is a mixture of graphene fiber and basalt fiber in a mass ratio of 3:2; the diameter of the mixed fiber is 10μm-1000μm; the length of the mixed fiber is 0.5cm-2cm; the wood particles are a mixture of camphor wood and oak in a weight ratio of 1:1; the average particle size of the wood particles is 5mm; the strength grade of the high-strength silicate cement is P.O52.5; the average particle size of the ore is 10mm; the average particle size of the perlite is 10mm;
[0120] A1. According to parts by weight, high-strength Portland cement, ore, ore sand, mixed fiber, epoxy resin adhesive, wood particles, composite plastic masterbatch, cut wire shot, iron powder, perlite and water were mixed and stirred for 10 minutes to obtain a mixed raw material;
[0121] A2. The mixed raw materials were vibrated at a frequency of 250 Hz for 3 minutes using a vibrating rod, and after 21 days of curing and watering 3 times a day, a mixed material was obtained.
[0122] Comparative Example 4
[0123] Preparation of mixture materials: Select raw materials by weight: 30 parts of high-strength silicate cement, 15 parts of ore, 18 parts of mineral sand, 2 parts of epoxy resin adhesive, 10 parts of wood particles, 10 parts of composite plastic masterbatch prepared in Example 1 of composite plastic masterbatch preparation, 7 parts of cut wire shot, 6 parts of iron powder, 9 parts of perlite, and 28 parts of water; wherein the wood particles are mixed with camphor wood and oak in a weight ratio of 1:1; the average particle size of the wood particles is 5mm; the strength grade of the high-strength silicate cement is P.O52.5; the average particle size of the ore is 10mm; the average particle size of the perlite is 10mm;
[0124] A1. According to parts by weight, high-strength Portland cement, ore, ore sand, epoxy resin adhesive, wood particles, composite plastic masterbatch, cut wire shot, iron powder, perlite and water were mixed and stirred for 10 minutes to obtain a mixed raw material;
[0125] A2. The mixed raw materials were vibrated at a frequency of 250 Hz for 3 minutes using a vibrating rod, and after 21 days of curing and watering 3 times a day, a mixed material was obtained.
[0126] Experimental example
[0127] The mixed materials prepared in Examples 1-3 and Comparative Examples 1-4 were tested for compressive strength, flexural strength, splitting tensile strength, and impact strength, respectively, and the test methods were as follows:
[0128] The compressive strength is tested according to GB / T 50081-2019;
[0129] The flexural strength is tested according to the standard of GB / T 50081-2019;
[0130] The splitting tensile strength is tested according to the standard of GB / T 50081-2019;
[0131] The test method of impact strength is as follows: the mixed material sample is made into a cube with a side length of 10 cm. This experiment adopts the drop hammer method for testing, in which the hammer weighs 3 kg, the lower end of the hammer is a spherical surface, and the drop height is 0.53 m. The impact resistance of concrete is expressed by the energy consumed per unit volume when the first visible crack appears on the surface of the sample under the repeated impact of the drop hammer. It is called impact strength and is expressed by the following formula: R 冲 =9.8GHn / V; where R 冲 -Impact strength (J / cm 3 ), G-impact hammer mass (kg), H-hammer drop height (m), n-impact number (times), V-sample volume (cm 3 ).
[0132] The test data is shown in Table 1 below:
[0133] Table 1
[0134]
[0135] It can be seen from Table 1 that the mixture materials prepared in Examples 1-3 of the present application have excellent compressive strength, flexural strength, splitting tensile strength, and impact strength, which improves the mechanical properties of concrete while improving its drop resistance.
[0136] The preparation raw materials of Comparative Example 1 do not contain composite plastic masterbatch, and the rest are the same as Example 1. The flexural strength, splitting tensile strength, impact strength and other properties of the mixture material prepared in Comparative Example 1 are obviously inferior to those of Example 1 of the present application, indicating that the composite plastic masterbatch prepared in the present application is very important for improving the performance of the mixture material. It not only has good elasticity, but also can be combined with other components to further improve the flexural resistance and drop resistance of the mixture.
[0137] The raw materials for preparing comparative example 2 are the composite plastic masterbatch prepared in comparative example 1. The modified nano zinc oxide in the raw materials for preparing the composite plastic masterbatch has not been treated with graphene, and the rest are the same as in Example 1. The flexural strength, splitting tensile strength, impact strength and other properties of the mixture material prepared in comparative example 2 are significantly inferior to those in Example 1 of the present application, indicating that the specific combination of components in the composite plastic masterbatch in the present application is very important for improving the performance of the mixture material. Graphene modification can make the nano zinc oxide filler and polycarbonate mixed more fully, thereby improving the performance of the composite plastic masterbatch and further improving the flexural and drop resistance of the mixture.
[0138] The raw materials for preparing the composite plastic masterbatch in Comparative Example 3 are the composite plastic masterbatch prepared in Comparative Example 2. The raw materials for preparing the composite plastic masterbatch do not contain silicone-modified polyurethane acrylate oligomers, and the rest are the same as Example 1. The flexural strength, splitting tensile strength, impact strength and other properties of the mixture material prepared in Comparative Example 3 are significantly inferior to those in Example 1 of the present application, indicating that the specific combination of components in the composite plastic masterbatch in the present application is very important for improving the performance of the mixture material. The silicone-modified polyurethane acrylate oligomer can well improve the compatibility of the components of the system, improve processing fluidity, improve the surface properties of the composite plastic masterbatch, and further improve the flexural resistance and drop resistance of the mixture.
[0139] The raw materials for the preparation of Comparative Example 4 do not contain mixed fibers, and the rest are the same as Example 1. The compressive strength, flexural strength, splitting tensile strength, and impact strength of the mixture material prepared in Comparative Example 4 are all poor, indicating that the mixed fibers of the present application are filled into the voids in the cement slurry, and epoxy resin adhesive is added for bonding. The epoxy resin adhesive can penetrate into the tiny pores of the concrete matrix, forming mechanical bite and chemical bonding with the concrete, thereby enhancing the bonding force between the fiber and the concrete, promoting the combination of the fiber and the cement, and enhancing the strength and stability of the mixture material.
[0140] Kettlebell Preparation Example 1
[0141] Kettlebell Preparation:
[0142] (1) welding the spherical frame and the U-shaped handle to make a frame; wherein the material of the frame is steel bars;
[0143] (2) Using the raw materials selected in Example 1, high-strength silicate cement, ore, mineral sand, mixed fiber, epoxy resin adhesive, wood particles, composite plastic masterbatch, steel wire shot, iron powder, perlite and water were mixed according to weight parts, and stirred for 10 minutes to obtain a mixed raw material;
[0144] (3) filling the skeleton and the mixed raw materials into a kettlebell mold, vibrating the mold at a frequency of 250 Hz for 3 minutes using a vibrating rod, curing the mold for 21 days and watering the mold 3 times a day to obtain a kettlebell core;
[0145] (4) Using a rubber coating mold to coat the outer layer of the kettlebell inner core by heating and vulcanization, wherein the upper mold temperature is 145° C., and the lower mold temperature is 145° C., to obtain a kettlebell; wherein the material of the rubber coating layer is rubber particles.
[0146] The prepared kettlebell was tested and found to be able to withstand 20,000 drops. It is strong, durable, has good vibration reduction effect, and will not cause damage to the ground.
[0147] Although the embodiments of the present application have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions or variations may be made to the embodiments without departing from the principles and purpose of the present application, and that the technical solutions after these changes, modifications, substitutions or variations will fall within the scope of protection of the present application.
Claims
1. A mixture material, characterized in that: The preparation comprises the following raw materials in parts by weight: 20-40 parts of high-strength Portland cement, 10-20 parts of ore, 10-20 parts of mineral sand, 5-10 parts of mixed fiber, 2-3 parts of epoxy resin adhesive, 5-15 parts of wood particles, 5-15 parts of composite plastic masterbatch, 5-10 parts of cut wire shot, 3-8 parts of iron powder, 5-15 parts of perlite, 20-40 parts of water; Wherein, the hybrid fiber comprises graphene fiber and basalt fiber in a mass ratio of (2-3):(1-2); The composite plastic masterbatch comprises the following raw materials in parts by weight: 40-45 parts of polycarbonate carrier resin, 1-2 parts of dispersant, 4-6 parts of aramid fiber, 1-2 parts of modified nano zinc oxide, and 2-3 parts of copolymerized methyl methacrylate; The dispersant is a silicone-modified polyurethane acrylate oligomer; The preparation method of the organosilicon-modified polyurethane acrylate oligomer comprises the following steps: 40-50 parts of polyurethane acrylate oligomer, 8-10 parts of pentaerythritol triacrylate, and 2-3 parts of 3-aminopropyltriethoxysilane are mixed according to weight parts, and heated in an oil bath at a speed of 200 rpm / min until the temperature reaches 150-160° C., and 0.3-0.6 parts of dicumyl peroxide solution are added dropwise at a speed of 30 drops / min. After reacting for 4-6 hours, a silicone-modified polyurethane acrylate oligomer is obtained; The preparation method of the modified nano zinc oxide comprises the following steps: B1. Ultrasonic dispersion of nano zinc oxide in a mixed solution of anhydrous ethanol and deionized water (8-9):1 mass ratio, and adding coupling agent KH-550 under stirring, raising the temperature to 70-80 ° C, constant temperature magnetic stirring for 5-8h, centrifugation, washing, and drying to obtain organosilicon-modified nano zinc oxide; B2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4h, and dried and ground after the reaction is completed; B3. Add the graphene pretreated in step B2 to ethanol for ultrasonic dispersion, add the organosilicon-modified nano zinc oxide prepared in step B1, stir rapidly at 25-35°C to allow it to react fully, centrifuge, wash several times with anhydrous ethanol, dry in vacuum, and grind to obtain modified nano zinc oxide.
2. A mixture material according to claim 1, characterized in that: The preparation method of the composite plastic masterbatch comprises the following steps: S1. According to the ratio of polycarbonate carrier resin, dispersant, aramid fiber, modified nano zinc oxide, copolymerized methyl methacrylate was added to a high-speed mixer and stirred evenly to obtain a granulation raw material; S2. The granulated raw materials in step S1 are subjected to twin-screw granulation to obtain composite plastic masterbatch.
3. A mixture material according to claim 1, characterized in that: In step B1, the mass ratio of the nano zinc oxide, the anhydrous ethanol and the coupling agent KH-550 is 1:(8-10):(0.1-0.2).
4. A mixture material according to claim 1, characterized in that: The wood particles are selected from at least one of ash, beech, camphor, walnut, oak, birch, fir, elm and red wood, and / or the average particle size of the wood particles is 3-6 mm.
5. A mixture material according to claim 1, characterized in that: The diameter of the mixed fiber is 10 μm-1000 μm, the length of the mixed fiber is 0.5 cm-2 cm, the average particle size of the ore is 5-15 mm, and the average particle size of the perlite is 5-15 mm.
6. A mixture material according to claim 1, characterized in that: The preparation method of the mixture material comprises the following steps: A1. According to parts by weight, high-strength Portland cement, ore, ore sand, mixed fiber, epoxy resin adhesive, wood particles, composite plastic masterbatch, cut wire shot, iron powder, perlite and water were mixed and stirred for 10 minutes to obtain a mixed raw material; A2. The mixed raw materials were vibrated at a frequency of 200-300 Hz for 2-4 minutes using a vibrating rod, and after 21 days of curing and watering 3 times a day, a mixture material was obtained.
7. A kettlebell comprising the mixture material according to any one of claims 1 to 6, characterized in that: The kettlebell comprises a frame and a rubber coating layer.
8. The kettlebell according to claim 7, characterized in that The material of the frame is steel bars; the frame comprises a spherical frame and a U-shaped handle.
9. The kettlebell according to claim 8, characterized in that The material of the rubber coating is selected from one of synthetic rubber, rubber particles and rubber plastic.
10. A method for preparing a kettlebell according to claim 9, characterized in that: The following steps are involved: (1) connecting the spherical frame and the U-shaped handle to form a frame; (2) mixing high-strength silicate cement, ore, mineral sand, mixed fiber, epoxy resin adhesive, wood particles, composite plastic masterbatch, cut wire shot, iron powder, perlite and water according to weight parts, and stirring for 10 minutes to obtain a mixed raw material; (3) filling the skeleton and the mixed raw materials into a kettlebell mold, vibrating the mold at a frequency of 200-300 Hz for 2-4 minutes using a vibrating rod, curing the mold for 21 days and watering the mold 3 times a day to obtain a kettlebell core; (4) Using a rubber coating mold to coat the outer layer of the kettlebell inner core by heating and vulcanization, wherein The upper mold temperature is 145°C, the lower mold temperature is 145°C, and a kettlebell is obtained.